Hospitalization and mortality trends among patients with confirmed COVID-19 in the United States, April through August 2020 - Jennifer Nguyen; Michael Benigno; Deepa Malhotra; Maya Reimbaeva; Ziphora Sam; Richard Chambers; Jennifer Hammond; Birol Emir (SAGE Publishing, 2021)
Background: The United States has experienced high COVID-19 case counts, hospitalizations, and death rates. This retrospective analysis reports changing trends in the demographics and clinical outcomes of hospitalized US COVID-19 patients between April and August 2020. Design and Methods: The Premier Healthcare Database Special Release was used to examine patient demographics of hospitalized COVID-19 patients from all US Census Bureau divisions. Demographics included age, sex, race, and ethnicity. Clinical outcomes included in-hospital mortality, intensive care unit (ICU) admission, and receipt of invasive mechanical ventilation. Results: Overall, 146,491 hospitalized COVID-19 patients were included (mean [SD] age, 61.0 [18.4] years; 51.7% male; 29.6% White non-Hispanic). Monthly total hospitalizations decreased from 44,854 in April to 18,533 in August; ICU admissions increased from 19.8% to 23.6%, and ventilator use and inpatient mortality decreased from 18.6% to 14.5% and 21.0% to 11.4%, respectively. Inpatient mortality was highest in the Middle Atlantic division (20.3%), followed by the New England (19.0%), East North Central (14.2%), and Mountain (13.7%) divisions. Black non-Hispanic patients were overrepresented among hospitalizations (19.0%); this group comprises 12.2% of the US population. Patients aged <65 years made up 53% of hospitalizations and had lower inpatient mortality than those aged ≥65 years. Conclusions: Hospitalizations, ventilator use, and mortality decreased, while ICU admission rates increased from April to August 2020. Older individuals and Black non-Hispanics were found to be at elevated risk of severe outcomes. These trends could inform ongoing patient care and US public health policies to limit the further spread of SARS-CoV-2.